Clinical impact of inherited and acquired genetic variants in mastocytosis - Nedoszytko, Bogusław; Arock, Michel; Lyons, Jonathan J.; Bachelot, Guillaume; Schwartz, Lawrence B.; Reiter, Andreas; Jawhar, Mohamad; Schwaab, Juliana; Lange, Magdalena; Greiner, Georg; Hoermann, Gregor; Niedoszytko, Marek; et al. (International journal of molecular sciences, 2021)
Mastocytosis is a rare and complex disease characterized by expansion of clonal mast cells (MC) in skin and/or various internal organ systems. Involvement of internal organs leads to the diagnosis of systemic mastocyt!1446321282!osis (SM). The WHO classification divides SM into indolent SM, smoldering SM and advanced SM variants, including SM with an associated hematologic neoplasm, aggressive SM, and MC leukemia. Historically, genetic analysis of individuals with pure cutaneous mastocytosis (CM) and SM have focused primarily on cohort studies of inherited single nucleotide variants and acquired pathogenic variants. The most prevalent pathogenic variant (mutation) in patients with SM is KIT p.D816V, which is detectable in most adult patients. Other somatic mutations have also been identified—especially in advanced SM—in TET2, SRSF2, ASXL1, RUNX1, CBL and JAK2, and shown to impact clinical and cellular phenotypes. Although only small patient cohorts have been analyzed, disease associations have also been identified in several germline variants within genes encoding certain cytokines or their receptors (IL13, IL6, IL6R, IL31, IL4R) and toll-like receptors. More recently, an increased prevalence of hereditary alpha-tryptasemia (HαT) caused by increased TPSAB1 copy number encoding alpha-tryptase has been described in patients with SM. Whereas HαT is found in 3-6% of general Western populations, it is identified in up to 17% of patients with SM. In the current manuscript we review the prevalence, functional role and clinical impact of various germline and somatic genetic variants in patients with mastocytosis.
Gesehen am 10.05.2021